Management Overconfidence and Co-Financing Decision in Tehran’s Securities Stock Exchange - Salami, Akbar; Aslizadeh, Ahmad; Asgari, Mohammad Reza (International Journal of Economics and Financial Issues, 2017)
The aim of this research is to determine the effect of management overconfidence and government interference on co-financing decision. This research in terms of the aim is applicable and in terms of the nature, it is descriptive-correlation. In order to test the hypotheses, regression model and data panel model were used for the period of 2011-2016 and this research annually studied a 136-company sample from the stocks of companies listed on Tehran’s securities stock exchange which were selected by systematic elimination method. To analyze the data, the econometric software of Eviews9 has been used. The results indicate that the management overconfidence influences on co-financing. The variables of the profile picture of managing director, managing director experience, managing director relation, ex- managing director performance and governmental ownership influence on co-financing decision. Also, the results indicated that the possessive structure of government moderates the relation between management overconfidence and co-financing decision. Keywords: Stock exchange, overconfidence, finance decision JEL Classifications: E44, G2